Transformativity: recognising melancholic power, and renegotiating vulnerability - Knowles, Corinne Ruth (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2010)
South African universities are embedded in an unequal society. Transformation strategies and interventions in the sector attempt to address this, but arguably, the policies and practices which aim to bring about transformation are merely platforms for potential change and do not guarantee the achievement of their aspirations. This study engages with the notion of transformation in one university, looking at how an organisation for women has contributed to transformation in individuals and in the institution. It explores the idea that vulnerability is the starting point of transformation, and must be recognized and incorporated into how an organisation, institution or individual regards vulnerable groups, in order to build a more equitable society. The reframing of vulnerability is a process of acknowledging the way power works, and arguably, power's melancholic nature and expression in society and in universities has particular challenges with regard to how vulnerable groups experience their vulnerability. If the framing of an individual as vulnerable does not also provide that individual with the conditions that shelter the vulnerability they experience, leading to a renegotiation of whom they can become, their "vulnerable" status is entrenched. The study explores ways in which an organisation for women uses its legitimized platform for renegotiating subjectivities, norms and performances, and the potential this has for transformativity.
Keywords: Transformational leadership -- South Africa|Educational change -- South Africa|Universities and colleges -- South Africa|Sex discrimination in higher education -- South Africa